2008
DOI: 10.1021/ma801152p
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of Polyethylenes Containing Chlorines: Precise vs Random Placement

Abstract: The crystallization behavior and crystalline structure of a series of chlorine-containing polyethylenes (PEs) with either a random or a precise placement of the Cl atom on each and every 21st, 19th, 15th, and 9th backbone carbon have been studied by DSC, NMR, Raman spectroscopy, WAXD, SAXS and AFM in samples cooled from the melt at 1°C/min. All precision Cl-substituted PEs crystallize as homopolymers based on their DD/MAS solid-state 13 C NMR spectra that reveal a uniform distribution of the content of halogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
72
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(78 citation statements)
references
References 36 publications
6
72
0
Order By: Relevance
“…21 The presence of the polar ImBr side groups, even when precisely spaced, disrupts the ability of these materials to crystallize and slows crystallization considerably. As expected, ionomers with longer ethylene spacer lengths (decreasing ion content) lead to slightly higher degrees of crystallinity (X c ) and melting temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…21 The presence of the polar ImBr side groups, even when precisely spaced, disrupts the ability of these materials to crystallize and slows crystallization considerably. As expected, ionomers with longer ethylene spacer lengths (decreasing ion content) lead to slightly higher degrees of crystallinity (X c ) and melting temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…The precise PE ionomers have been extensively characterized using X-ray scattering, scanning electron microscopy, NMR [7,12]. The crystallization and segmental dynamics as a function of random versus precise functional group spacing has been probed using 13 C, 19 F and 31 P MAS NMR [7,8,13,14], high-speed 1 H MAS NMR [15], and static 2 H NMR [9]. For the present study, characterization of the heterogeneous carboxylic acid proton environments observed for both the precise and random P(E-AA) materials is of interest.…”
Section: Introductionmentioning
confidence: 99%
“…demonstrated that the folding behavior of polyethylene‐like polymers can be controlled by placing bulky substituents at periodically along the polymer backbone, which served as a folding controller . Similarly, research groups of Wagener, Winey, Mecking, and others studied folding of polyethylene‐like chains by periodic placement of hexyl, oligoethylene glycol, sulfonate or even chloro‐ substituents, along the backbone . They also demonstrated the profound effect of periodicity of the substituent on the folding behavior and the lamellar dimensions; in case of randomly distributed branch points, the polymers were found to exhibit curved and segmented morphologies .…”
Section: Introductionmentioning
confidence: 96%